PAPILIO DEMOLEUS L. AND PAPILIO POLYTES L. (LEPIDOPTERA: PAPILIONIDAE) REARED ON SOME HOST PLANTS AT BUTTERFLY RESEARCH FACILITY, LIPI - CIBINONG, WEST JAVA, INDONESIA - Djunijanti Peggie; Supadi Supadi; Guntoro Guntoro; Sarino Sarino; Fatimah Fatimah; Rina Rachmatiyah; Christoph L. Häuser (Treubia, 2022)
Papilio demoleus L. and P. polytes L. are common butterflies and distribute almost throughout Indonesia. Both species are attractive in butterfly gardens, but may be considered as pests in Citrus plantations. This research aimed to obtain data on their biology, on how the species thrive in captivity, and to assess the alternative host plants. Captive breeding research on these two species was conducted at the butterfly research facility within the period of September 2016 to February 2019, with 482 individuals of P. demoleus and 2,334 individuals of P. polytes reared, of which 292 individuals of P. demoleus and 560 individuals of P. polytes have complete informative data. The average duration of eggs was 3.7 days for P. demoleus on Citrus spp., 3.68 days for P. polytes on Citrus spp., and 3.48 days for P. polytes on Micromelum minutum. The duration of larvae varied between 13–19 days for both species. Prepupal stage lasted for 1 day for all observed individuals. Incidental observation at home during the pandemic COVID-19 added some insights that the pupation happened between 18:00-19:00. The duration of pupae varied between 9–14 days for both species. The total duration of pre-adult stages for both species was between 26–38 days. Adults at the butterfly dome could live up to 19 days for P. demoleus and 39 days for P. polytes. Recognition of alternative host plants is very useful for the improvement of species management in butterfly gardens and in Citrus plantations.